2019
DOI: 10.3892/mmr.2019.10718
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine protects against sepsis‑associated encephalopathy through Hsp90/AKT signaling

Abstract: Sepsis-associated encephalopathy (Sae) is characterized by neuronal apoptosis and changes in mental status. accumulating evidence has. indicated that dexmedetomidine is capable of protecting the brain against external stimuli and improving cognitive dysfunctions. The aim of the present study was to investigate the possible neuroprotective effects of dexmedetomidine on Sae and the role of heat-shock protein (Hsp)90/aKT signaling in an experimental model of sepsis. The Sae model was established by cecal ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have suggested the neuroprotective effects of DEX in various models. [31][32][33][34] In recent years, researchers found that DEX inhibited lidocaine-induced neurotoxicity. 16,17,23 In this study, we also verified the role of SIRT1/FOXO3a signaling in the effect of DEX on lidocaine-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the neuroprotective effects of DEX in various models. [31][32][33][34] In recent years, researchers found that DEX inhibited lidocaine-induced neurotoxicity. 16,17,23 In this study, we also verified the role of SIRT1/FOXO3a signaling in the effect of DEX on lidocaine-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells affect the expression of inflammatory factors, which can trigger the CNS response and amplify neuroinflammation through vagal afferents or BBB ( 61 , 62 ). The inflammatory cells in CNS release more inflammatory cytokines which concentrate in specific brain regions, leading to the occurrence of POCD ( 37 , 63 , 64 ) and resulting in the development of neurodegenerative diseases ( 65 ). The present results indicated that DEX decreased the occurrence of POCD, which could be related to the effect of DEX on perioperative immune function and potential neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The Hsp90 modulates cell apoptosis and is essential for Akt to regulate cell growth, cell survival, and cell differentiation. Clinically, dexmedetomidine improved emotional and cognitive functions in rodents (Ning et al, 2017;Yeh et al, 2018;Yin et al, 2019).…”
Section: Neuroprotective Effect Of Dexmedetomidine In Neuroinflammatory Modelmentioning
confidence: 93%
“…Pretreatment with dexmedetomidine reduced microglial activation, which produces proinflammatory cytokines and ROS, resulting in reduced inflammation, apoptosis, and sickness behaviour in mice (Yeh et al, 2018). Posttreatment with dexmedetomidine reduced hippocampal apoptosis in rats by upregulating the Hsp/Akt signalling pathway (Yin et al, 2019). The Hsp90 modulates cell apoptosis and is essential for Akt to regulate cell growth, cell survival, and cell differentiation.…”
Section: Neuroprotective Effect Of Dexmedetomidine In Neuroinflammatory Modelmentioning
confidence: 99%
See 1 more Smart Citation